3D multi-scale segmentation of granular materials - Tariel, Vincent (Image analysis and stereology, 2008)
On a microscopic scale, a pyrotechnic material is made of a polymer matrix containing grains with different sizes and shapes. Its physical behaviour can be predicted by homogenization. Information about the morphology of the grainscan be obtained by different ways. One of these ways is 3D image processing. This has been made easier by the use of a new imaging technique, the microtomography, allowing fast threedimensional reconstruction and processing. In this paper images of two granular materials are segmented by means of 3D mathematicalmorphology algorithms, based on a multi-scale extraction of markers for watershed segmentation.
Keywords: Materiali, testiranje; Particle Size; Slika, obdelava z računalnikom; Materials Testing; Delec, velikost; Image Processing, Computer-Assisted; delci; morfologija; tomografija; segmentacija